Antimicrobial activity of TiO2 nanoparticle-coated film for potential food packaging applications - Othman, Siti Hajar; Abd Salam, Nurul Raudhah; Zainal, Norhazlizam; Kadir Basha, Roseliza; A. Talib, Rosnita (Hindawi Publishing Corporation, 2014)
Recent uses of titanium dioxide (TiO2) have involved various applications which include the food industry. This study aims to develop TiO2 nanoparticle-coated film for potential food packaging applications due to the photocatalytic antimicrobial property of TiO2. The TiO2 nanoparticles with varying concentrations (0–0.11 g/ 100 mL organic solvent) were coated on food packaging film, particularly low density polyethylene (LDPE) film. The antimicrobial activity of the films was investigated by their capability to inactivate Escherichia coli (E. coli) in an actual food packaging application test under various conditions, including types of light (fluorescent and ultraviolet (UV)) and the length of time the film was exposed to light (one–three days). The antimicrobial activity of the TiO2 nanoparticle-coated films exposed under both types of lighting was found to increase with an increase in the TiO2 nanoparticle concentration and the light exposure time. It was also found that the antimicrobial activity of the films exposed under UV light was higher than that under fluorescent light. The developed film has the potential to be used as a food packaging film that can extend the shelf life, maintain the quality, and assure the safety of food.